Tf2O-Induced C(sp2)-N(sp2) bond formation: one-pot synthesis of N-heteroarene quaternary salts in nonbenzenoid skeleton of tropolone alkaloids under mild reaction conditions - Lohote, Mahendra V.; Bhattacharya, Asish K. (Organic Letters, 2025)
Naturally occurring protoalkaloids, such as colchicine and colchicoside, have significant medical applications and are used globally to treat a variety of diseases. We report herein a C(sp2)-N(sp2) bond formation protocol via a Tf2O (triflic anhydride)-assisted one-pot aromatic nucleophilic substitution (SNAr) reaction on various naturally occurring biologically active compounds such as colchicine, 3-demethyl colchicine, and 2-methoxy tropone under mild reaction conditions. Synthesis of bench-stable heterotropone quaternary salts was achieved by the reaction of tropolone alkaloids with diverse non-nucleophilic N-heterocycles. The developed methodology demonstrates wide substrate scope with good to very good yield. Our devised approach paves the way for future drug design efforts involving bioactive natural products with tropolone skeletons.